PSPICE modelling and design of a snubber circuit for the matrix converter - Sünter, S.; Tatar, Y. (University of Split, 2000)
In matrix converters one of the basic commutation strategies is the dead time current commutation. Although the application of this commutation strategy is simple and easy, the design of snubber parameters becomes crucial to control the voltage spikes across the switches due to the open circuiting of the motor winding during the dead time. This paper deals with the design of a simple snubber circuit for the matrix converter. Complicated power circuit of the converter and its operation make the design of the snubber circuit difficult even for a simple snubber arrangement. The matrix converter power circuit applying dead time strategy is built up from 9-bidirectional switches and each switch should have a snubber due to the absence of freewheeling paths. In this work, an R-C turn-off snubber circuit connected across to each bidirectional switch is used to limit the device voltage to an appropriate level. This snubber arrangement has been analyzed and then the PSPICE modelling of the matrix converter including snubbers has been performed for various operating conditions. A 2.2 kW matrix converter power circuit using IGBT devices has been constructed by considering the analysis and simulation results. Experimental results are presented to confirm the theoretical results and therefore to correct operation of the system.
Keywords: Matrix converter; PSPICE; Snubber circuit